Rancang Bangun Aplikasi M-Feedback Pada PT Asus Service Indonesia Batam: Design; Application; M-Feedback; Web-Based - tukino tukino (Computer Based Information System Journal, 2019)
Today the development of technology is growing very rapidly. The existence of the development of information technology is able to facilitate the activities in daily life. In every agency in general has applied information technology to help improve the performance of its activities. PT Asus Service Indonesia Batam is one company engaged in the field of electronic customer Service. The company only serves repair and component testing, such as motherboards on laptops and PCs as well as maintenance and development of electronic components. PT ASID still lacks responses about the complaints of its employees, such as limited requests for tools (tool) and some Service companies that are less adequate, resulting in hampering work processes and employee performance. To overcome this problem, the author designed a web-based m-Feedback application to facilitate employees in giving complaints and to find out how to implement m-Feedback application on PT Asus Service Indonesia Batam . The research method used is waterfall method consisting of needs analysis , design, coding, testing, and support or maintenance. The result of this research is web design m-Feedback application at PT Asus Service Indonesia Batam, where the application can facilitate the company in obtaining Feedback information provided by the employees quickly and accurately and facilitate the employees to deliver Feedback to the company.